2017
DOI: 10.1002/cncr.31193
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes enhance the survival prediction of traditional disease risk classifications: An international study in patients with myelodysplastic syndromes

Abstract: The FA-IPSS(h) is a novel patient-centered prognostic index that includes patients' self-reported fatigue severity. The authors believe its use might enhance physicians' ability to predict survival more accurately in patients with advanced MDS. Cancer 2018;124:1251-9. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Based on this evidence, fatigue might be considered a standard stratification factor in future [ 34 ]. Moreover, prediction of clinical outcome might be improved by the combination of disease- and patient-related factors resulting in an integrated prognostic model as recently demonstrated in MDS [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this evidence, fatigue might be considered a standard stratification factor in future [ 34 ]. Moreover, prediction of clinical outcome might be improved by the combination of disease- and patient-related factors resulting in an integrated prognostic model as recently demonstrated in MDS [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of symptoms and impairments was classified in three categories: not at all (0), mild (1–66), and moderate to severe (67–100) [ 6 , 16 ]. To analyze the impact of fatigue on clinical outcome, fatigue was divided in two categories as recently suggested by Efficace et al: no or mild versus strong fatigue with a cut-off at 45 on the EORTC QLQ-C30 scale (ranging from 0 = no symptom to 100 = strong symptom) [ 17 ]. The MGA included 13 questionnaires assessing performance status (WHO, Karnofsky), comorbidities (CCI, HCT-CI, CIRS-G), nutritional status (MNA), mental state (MMSE, GDS), social support (FSozu), functional capacities (IADL, ADL, TUG), and the screening tool G8.…”
Section: Methodsmentioning
confidence: 99%
“… 43‐46 A randomized trial showed that screening for these symptoms was associated with a 7‐month survival advantage over usual care, which in part may have been because patients in the intervention group had better performance status at progression and thus were more likely to receive optimal treatment 46,47 . Finally, several studies have shown that PROs enhance prediction of survival in myelodysplastic syndromes, 48 multiple myeloma, 49 early‐stage colorectal cancer, 50 advanced breast cancer, 51 metastatic castration‐resistant prostate cancer, 52 metastatic renal cell carcinoma, 53 advanced cancers, 54,55 and a variety of tumor types 56,57 . In fact, some data suggest that PROs predict survival better than provider‐rated performance status 58 …”
Section: The Need For Pghd In Cancer Carementioning
confidence: 99%
“…17,18 Still, intervention studies are sparse, and the use of PRO to improve treatment of hematological malignancies has not been well established. [19][20][21][22][23] In 2011-2012, the Blood Cancer Registry 24 decided to start a pilot project using PRO in the acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) registries. This pilot project was introduced as a clinical prospective study with the dual aim to evaluate both feasibility and the actual results.…”
Section: Introductionmentioning
confidence: 99%